Інтегрований погляд на сучасний стан забруднення атмосферного повітря в Україні (за матеріалами наукового повідомлення на засіданні Президії НАН України 12 липня 2023 р.) - Савенець, М.В. (Вісник НАН України, 2023)
Доповідь присвячено аналізу нинішнього стану забруднення атмосферного
повітря над територією України, здійсненому на основі інтегрованого використання даних наземних спостережень, супутникового зондування та
чисельного моделювання атмосферних процесів з урахуванням аерозольних ефектів. Розглянуто статистичні характеристики концентрацій
основних забруднюючих речовин на постах наземного моніторингу. Показано та обґрунтовано узгодженість даних із даними супутника Sentinel-5
Precursor. Продемонстровано можливості онлайн-інтегрованого чисельного моделювання на прикладі використання моделі Enviro-HIRLAM. The article is devoted to the analysis of modern atmospheric air pollution conditions over Ukraine based on the integrated
use of ground-based observations, remote sensing, and numerical atmospheric modeling including aerosol effects.
Ground-based monitoring data were used for detecting average air pollution in cities, the frequency of threshold level
exceedance, and comparing tendencies with national inventories. By applying meteorological data, the dependencies of
air pollution on atmospheric transport were estimated for every monitoring site (129 in total) in urban areas. In comparison
to point measurements, remote sensing data provides a detailed view covering the entire Ukrainian territory.
Using the automatic near-real-time system for the Sentinel-5P satellite, which was developed at the Ukrainian Hydrometeorological
Institute, we are able to analyze spatial and temporal features in remote regions and detect the consequences
of emissions including those from wildfires, dust storms, industrial objects, transboundary pollution, and waroriginated
sources. Numerical modeling makes it possible not only to simulate past air pollution distribution but also to
create air quality forecasts. Nowadays, we are using high-performance computing by running the online-integrated Enviro-
HIRLAM model to study pollution effects (mainly direct and indirect aerosol effects) on meteorological processes.
All these data sources together provide the only possible way to implement an integrated view of air pollution.